PENGARUH PENDEKATAN PEMBELAJARAN INDUKTIF TERHADAP HASIL BELAJAR EKONOMI SISWA - Riska Purnama Sari Tarigan (EDUCATE, 2025)
This study aims to determine the Effect of the Inductive Learning Approach on the Economics Learning Outcomes of Class X Students of SMA PAB 9 Patumbak. This study is associative, namely research that aims to determine the effect of two or more variables. This study uses a field study approach, namely a study based on facts that occur in the object of research. The population in this study were 28 students of Class X SMA PAB 9 Patumbak. The research sample that will be used in this study were 28 students of Class X SMA PAB 9 Patumbak. The analysis technique used is simple regression analysis and hypothesis testing. The suitability test using simple linear regression and hypothesis testing (t-test) was carried out to determine the Effect of the Inductive Learning Approach on the Economics Learning Outcomes of Class X Students of SMA PAB 9 Patumbak. Based on the hypothesis test, it is known that there is a positive influence between the Inductive Learning Approach on the Learning Outcomes of the Economics Subject of Class X at SMA PAB 9 Patumbak, this is evidenced by the t-value of the Inductive Learning Approach variable of 3.688. This means that the t-count value is greater than the t-table (3.688 < 1.705) which indicates that the Inductive Learning Approach has a positive effect on Student Learning Outcomes.